Influence of Leadership Style and Managerial Competence of School Principals on Teacher Performance Through Interpersonal Communication Based on Stifin - Karmilah Ilyas; Uli Wildan Nuryanto; Yolla Sukma Handayani (Jurnal Lingua Idea, 2026)
This research aims to analyze and measure teacher performance as assessed by school principals in an educational institution. Where what is done is how the leadership style and managerial competence of the school principal through interpersonal communication based on the STIFIn concept affects the performance of teachers at Integrated Islamic Schools in Cilegon City. This research is a type of qualitative descriptive research, where research is carried out by collecting and analyzing data such as interviews, observations and document analysis. The results of our research are how the principal sees a case in which each teacher has varying performance, some of the teachers' performance complies with institutional rules, some lack discipline, lack of understanding of communication, and there are still teachers who cannot work as a team well. There are also teachers who ignore time. Therefore, researchers see this as more important and more important to measure the performance of teachers/employees which will later be used as a comparison before supervision is carried out and after supervision is carried out. Where we hope by measuring the extent to which hopes and achievements can be in accordance with what is expected, namely with the Vision and Mission that exists and applies in the school. Hopefully it can inspire and become a benchmark in the same experience.